A URN-based methodology for business process monitoring - Pourshahid, Alireza (University of Ottawa (Canada), 2008)
Business Process Management Systems (BPMS) are attracting much attention these days as core tools for process management. A BPMS consists of several modules including Business Activity Monitoring (BAM), which evaluates the performance of processes. Although measuring the performance of business processes is based on organizational goals and the impact of processes on such goals is an important aspect of the process evaluation, most of the existing BPMS do not offer appropriate capabilities. Several process improvements and quality methodologies have also been around for some time. Most of them, however, are based on statistical and management tools that are not integrated with current technologies including BPMS. In other words, the management and quality disciplines have not yet evolved to take full advantage of current technologies that can enhance process improvement efforts. One of the pitfalls here is the failure to use the information generated by different information systems dispersed across the organization to evaluate the impact of processes on their goals. In this thesis, we use the User Requirements Notation (URN) in a methodology for evaluating business processes against organizational goals. Although URN enables the modeling of processes and goals, its process monitoring capabilities need enhancements and we will address this issue by extending URN. In addition, we propose a methodology that exploits the new capabilities of URN for process analysis and improvement. Unlike other quality methodologies, the methodology and supporting tool proposed are capable of using different sources of information to measure the performance of modeled processes and evaluate their impact on the goal models. The new capabilities and their benefits are illustrated through examples from the healthcare domain.
Keywords: Business Administration, Management.; Information Science.